Control interno en el proceso de cobranza y su incidencia en la liquidez de un vivero del sector Vía Daule - Alava Heredia, Mirelli Xiomara (2024)
Internal control focuses on how a directive or order is crucial within the various operations that are develop within a company, searching to play an essential role in consolidating of a well forged business management by identifying possible areas that are susceptible to some kind of improvement with the objective of generating a financial increase for the entity. In collections, internal control plays a fundamental role in maintenance of liquidity, since it establishes rules and procedures that allow guaranteeing a correct management of a company's resources, contributing to the identification and mitigation or reduction of possible financial risks. In this research work, weaknesses were identified, which are derived from the accounts receivable, the nursery doesn’t have a manual where the existence of collection policies is correctly stated, which generates a significant deficiency in the collection process. This caused the presence of overdue portfolios, since customers weren´t committed to payment of their obligation, so measures were sought to reduce these portfolios in order to obtain a positive result within the corresponding collection of overdue portfolios. An efficient collection process will ensure a steady flow of cash, which will allow the nursery to cover its expenses without the presence of significant conflicts.